Rancang Bangun Knowledge Management system pada Komisi Penyiaran Indonesia Daerah Sumatera Selatan menggunakan metode Prototype : Design and build a Knowledge Management system at the Indonesian Broadcasting Commission for the South Sumatra Region using the Prototype method - Mohammad Faris; Zaid Amin (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
AbstractProblems that often occur at the Indonesian Regional Broadcasting Commission (KPID) South Sumatra are related to finding information/technical documentation such as broadcasting manual documentation, broadcasting station problem logs, meeting documentation, employee training documentation and other documentation. Therefore, the existence of this KMS application can facilitate in overcoming documentation problems and improve the quality of employee work. In addition, the purpose of this KMS application is so that the knowledge possessed by each employee does not just disappear and can also be shared with other employees, as well as the creation of a means of communicating problems, as well as knowledge that is still stored in each employee so that there is no repetition of mistakes made. ever done. The result of this research is to design a web-based knowledge management system application that will be implemented at the Indonesian Regional Broadcasting Commission (KPID) South Sumatra. In this study, the author uses a prototype-based system development method, where this method is carried out to the prototype testing stage at the Indonesian Regional Broadcasting Commission (KPID) South Sumatra. Based on these problems, it encourages the idea of ​​developing a web-based knowledge management system application that will be implemented at the Indonesian Regional Broadcasting Commission (KPID) of South Sumatra with the research title, namely Design and Build a Knowledge Management System at the Indonesian Broadcasting Commission of South Sumatra using the Prototype Method. Keywords: Knowledge management system, Prototyping, Web Based, MySQL, PHP